САЛЫСТЫРМАЛЫ ТИПОЛОГИЯЛЫҚ ИЗЕРТЛЕЎ МӘСЕЛЕЛЕРИ - Бекбергенова, М.Д. (FAN va JAMIYAT, 2019)
The article is devoted to the issues of comparative typological study of literature. There are given definitions of concept «typological relationships». The author gives a review of scientific papers on the issues of comparative typological relations of academician A.N.Veselovsky, B. Zhirmunskiy, N. Konrad and others. There were analyzed the research works on the problem of comparative typological studies in Karakalpak prose. The questions of typological relations in Karakalpak prose of the twentieth century have been studied.